Significance of apparent diffusion coefficient in diagnosis of rectal carcinoma - Šarošković, Milica; Vuković, Miloš; Stojanoski, Stefan; Zorić, Milica; Prvulović Bunović, Nataša; Spirovski, Milena; Nosek, Igor (Frontiers in Oncology, 2024)
IntroductionThe apparent diffusion coefficient (ADC) is a quantitative parameter that facilitates the detection and reliable differentiation of rectal cancer. MR differentiation between rectal carcinoma, post-radiation proctitis, and normal rectal wall with the ADC values and their comparison depending on the level of tumor markers and pathohistological characteristics of rectal carcinoma.MethodsThe retrospective study performed at the Oncology Institute of Vojvodina included 300 patients, 100 each with rectal cancer, post-radiation proctitis, and normal rectum. Mean ADC values were obtained by measuring the region of interest (ROI) of the rectal wall.ResultsRectal cancer showed lower ADC values (0.665 ± 0.086 x 10-3mm2/s) compared to both post-radiation proctitis (1.648 ± 0.268 x 10-3mm2/s) and normal rectum (1.180 ± 0.110 x 10-3mm2/s) (p<0.001). No significant differences in ADC values were observed between different grades of rectal cancer (p=0.874; p>0.05), depending on the presence of metastases in the lymph nodes (p=0.357; p>0.05), different TN stage (p=0.196; p>0.05), local spread of the tumor (p=0.312; p>0.05), the presence of RAS mutation (p=0.829; p>0.05) and the value of tumor markers (p=0.923; p>0.05). ADC values below 1.013 x 10-3mm2/s with 100% sensitivity and 96% specificity indicate the presence of rectal cancer in relation to normal wall, with a positive predictive value of 96.1% and a negative of 100%. ADC values below 1.255 x 10-3mm2/s with 100% sensitivity and 95% specificity indicate rectal cancer in relation to post-radiation proctitis. ADC values above 1.339 x 10-3mm2/s with 87% sensitivity and 89% specificity indicate post-radiation proctitis in relation to normal wall.DiscussionThe ADC is a useful marker in differentiating between rectal cancer, post-radiation proctitis, and normal rectal wall with high sensitivity and specificity, but it cannot be used to distinguish the histological grades of rectal cancer, nor other pathohistological parameters.